Corruption as a media spectacle: An Analysis of Veja Magazine’s Covers about Operation Lava Jato - Ladeira-Mota, Célia (2017)
This article proposes an analysis of the covers of Veja magazine on the activities of Operation Lava Jato — investigation of the Federal Police and the Federal Public Ministry. The intention of the study is not to exhaust the subject, but to discuss the social and political meanings produced by the narratives. Our hypothesis is that in addition to working on the spectacularization of corruption as news-value, Veja actively participates as an actor in the political game, not only being an observer of the crisis settled in Brazil, but encouraging the population to take to the streets and fight against governments and politicians in general.